PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DALAM MENINGKATKAN MINAT BELAJAR BAHASA INDONESIA DI SD - Irvan, Moh. Farizqo; Wulandari, Dyah Ayu; Sasqia, Laely Ayu Candra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of technology-based learning media in increasing interest in learning Indonesian among elementary school students. The applied research approach is a descriptive qualitative case study. The subjects in this study were the principal, teachers, and fifth-grade students at SD Negeri Wates 02 Semarang. Data were collected through three techniques: interviews, observation, and documentation. Data were analyzed using descriptive methods, with data validity assessed through triangulation of sources and techniques. The results of the study indicate that 1) the use of technology-based learning media in Indonesian language learning has been implemented at SD Negeri 02 Wates which is adjusted to the needs and situations, 2) there are four main challenges in the application of technology-based learning media in Indonesian language learning, and 3) the use of technology-based learning media in Indonesian language learning has a positive impact on students' learning interest. Based on the findings of this study, it is recommended that technology-based learning media for Indonesian language instruction in elementary schools be developed for other subjects, while still paying attention to the school's needs and conditions, particularly regarding infrastructure availability and teacher competences.